Electric Field Characteristics of HDPE-NR Biocomposite under Breakdown Condition using COMSOL - Jerferi, Muhammad Syahmi; Mohd Jamail, Nor Akmal; Kamarudin, Qamarul Ezani (Evolution in Electrical and Electronic Engineering, 2022)
For the creation of future electrical networks, it was crucial to creating novel insulating materials that can enhance the performance of high voltage cables of the next generation. The high electric field reduces the resistance of solid insulation and induces partial discharge through dielectric flaws, leading the dielectric to degrade over time and eventually fail. This project aims to analyse the electric field intensity of High-Density Polyethylene (HDPE) in breakdown conditions when added with 10g, 20g, and 30g of various types of bio-filler, including oil palm empty fruit bunch, pineapple leaves fibre and coconut coir fibre. Using the COMSOL Multiphysics software, a two-dimensional (2D) axisymmetric electrostatic model can be generated. According to the results, the unfilled HDPE biocomposites have a higher electric field intensity than the 10g, 20g, and 30g biocomposites, with values of 25.70 MV/m and 32.51 MV/m for a needle to needle and sphere to sphere, respectively. Under breakdown conditions, the maximal electric field strength varies according to the permittivity and voltage of the bio-filler. Therefore, the maximum electric field intensity was dramatically reduced for HDPE containing 20g of pineapple leaves fibre, with values of 2.83 MV/m and 4.39 MV/m for a needle to needle and sphere to sphere, respectively. Consequently, pineapple leaf fibre was the optimal composition, since it tends to improve the dielectric characteristics due to its lower electric field intensity at the top electrode compared to other compositions